Implication of Ceramide Kinase in Adipogenesis - Marta Ordoñez; Natalia Presa; Miguel Trueba; Antonio Gomez-Muñoz (Hindawi Limited, 2017)
Ceramide kinase (CerK) plays a critical role in the regulation of cell growth and survival and has been implicated in proinflammatory responses. In this work, we demonstrate that CerK regulates adipocyte differentiation, a process associated with obesity, which causes chronic low-grade inflammation. CerK was upregulated during differentiation of 3T3-L1 preadipocytes into mature adipocytes. Noteworthy, knockdown of CerK using specific siRNA to silence the gene encoding this kinase resulted in substantial decrease of lipid droplet formation and potent depletion in the content of triacylglycerols in the adipocytes. Additionally, CerK knockdown caused blockade of leptin secretion, an adipokine that is crucial for regulation of energy balance in the organism and that is increased in the obese state. Moreover, CerK gene silencing decreased the expression of peroxisome proliferator-activated receptor gamma (PPARγ), which is considered the master regulator of adipogenesis. It can be concluded that CerK is a novel regulator of adipogenesis, an action that may have potential implications in the development of obesity, and that targeting this kinase may be beneficial for treatment of obesity-associated diseases.